On the Generalized Mittag-Leffler Function and its Application in a Fractional Telegraph Equation - Camargo, Rubens de Figueiredo [UNESP]; de Oliveira, Edmundo Capelas; Vaz, Jayme (Springer, 2012)
The classical Mittag-Leffler functions, involving one- and two-parameter, play an important role in the study of fractional-order differential (and integral) equations. The so-called generalized Mittag-Leffler function, a function with three-parameter which generalizes the classical ones, appear in the fractional telegraph equation. Here we introduce some integral transforms associated with this generalized Mittag-Leffler function. As particular cases some recent results are recovered.
Keywords: Fractional calculus; Mittag-Leffler functions; Integral transforms; H-Fox function